Coseismic Deformation Responses due to Geometrical Structure and Heterogeneity of the Accretionary Wedge: Study Case 2010 Mentawai Earthquake, West Sumatra, Indonesia - Alvina K. Kuncoro; Wahyu Srigutomo; Umar Fauzi (International Journal of Geophysics)
The assumption of a homogeneous elastic half-space model is widely used to model the earth’s deformation. However, the homogeneous assumption would not accurately reflect the complexity of the shallow crust. We performed a 3D coseismic deformation model using the finite element method and referred to the 2010 Mentawai earthquake. The 2010 tsunami earthquake was located at the Mentawai segment, which is a part of the accretionary wedge in the Sumatra subduction zone. This active accretionary wedge is identified as the most complicated structure on earth and lies along the Sumatra subduction zone, at which most destructive earthquakes happen in this region. We examined the impact of the accretionary wedge geometry and material properties by considering the wedge as a single different property separated from the continental plate. Various geometrical features, such as topography and wedge dimension, as well as physical properties, were simulated. Those features are then observed for their responses on the surface deformation. The topography affected the magnitude of the horizontal deformation up to 10% but only the pattern of the vertical deformation. The wedge dimension seems to have an insignificant influence on the surface deformation compared to the topography. Different physical properties of the accretionary wedge affect not only the magnitude of the horizontal deformation up to 40% but also the orientation. The direction of the lateral movement is seemingly affected by the material under the GPS station and by the source. On the other hand, the variations in the physical properties resulted in discrepancies of 0.5 meters in the vertical deformation near the source. These results indicated that regional physical property information and geometrical features are critical in estimating coseismic deformation, leading to more accurate slip inversion and earthquake and tsunami hazard prediction, particularly in regions with significant inhomogeneity.